The Role of the Decrees of Peter the Great in the Formation and Development of Russian Pharmacy. Part 1 - K. S. Guzev (Разработка и регистрация лекарственных средств)
The first part of the article, based on a systematic analysis of the decrees of Peter the Great, presents the steps of the Russian Emperor to establish and develop the pharmacy service in Russia are given. An analysis of the text of the decrees shows that Peter the Great's special interest in the distribution of medicines appeared from the end of the 17th to the beginning of the 18th century, after his first visit to Europe. His first step, aimed at controlling the distribution of medicines, was the Decree to the customs service on the need to inspect and send to Moscow pharmaceutical supplies brought from abroad. Having gained control over the import of medicines and their monopoly distribution, Peter the Great organized the delivery of medicines from the royal pharmacy to the army. The Emperor’s next step was the foundation of a network of Moscow pharmacies. To do this, he issued a Decree on the establishment of eight pharmacies in Moscow. Later, such pharmacies were also established in St. Petersburg and other major Russian cities. Peter the Great gave the owners of these pharmacies nominal letters designed to protect them from excessive extortion and injustice of the city authorities. It was necessary to establish the supply of the new pharmacies with the appropriate raw materials. Peter the Great, by his decrees, ordered to purchase medicinal herbs collected in Siberia, to create pharmacy gardens in Moscow, St. Petersburg and Astrakhan, and to restrict trade in certain important goods. In addition, according to the decree of Peter the Great, scientific expeditions are sent around Russia to search for mineral water and explore the riches of Siberia.